Three new species of Freycinetia (Pandanaceae) from Kalimantan, Indonesia - Ary Prihardhyanto Keim (Research Center for Biology, 2009)
Three new species of Freycinetia (Pandanaceae) from Kalimantan (Indonesian Borneo) are firstly described in this paper namely F. kartawinatae A.P. Keim, F. runcingensis A. P. Keim, and F. subracemosa A.P. Keim.